Chaperone-Mediated Regulation of Choline Acetyltransferase Protein Stability and Activity by HSC/HSP70, HSP90, and p97/VCP - Morey, Trevor M.; Winick-Ng, Warren; Seah, Claudia; Rylett, R. Jane (Frontiers in Molecular Neuroscience, 2017)
Choline acetyltransferase (ChAT) synthesizes the neurotransmitter acetylcholine in cholinergic neurons, and mutations of this enzyme are linked to the neuromuscular disorder congenital myasthenic syndrome (CMS). One CMS-related mutation, V18M, reduces ChAT enzyme activity and cellular protein levels, and is located within a highly-conserved N-terminal proline-rich motif at residues 14PKLPVPP20. We showed previously that disruption of this proline-rich motif by either proline-to-alanine mutation (P17A/P19A) or mutation of residue Val18 (V18M) enhances ubiquitination and degradation of these mutant ChAT proteins expressed in cholinergic SN56 cells by an unknown mechanism. In this study, using proximity-dependent biotin identification (BioID), co-immunoprecipitation and in situ proximity-ligation assay (PLA), we identified the heat shock proteins (HSPs) HSC/HSP70 and HSP90 as novel ChAT protein-interactors. These molecular chaperones are well-known for promoting the folding and stabilization of cellular proteins. Thus, we found that inhibition of HSPs by treatment of cells with either the HSC/HSP70 inhibitors 2-phenylethynesulfonamide (PES) or VER-155008, or the HSP90 inhibitor 17-AAG reduced cellular ChAT activity and solubility, and enhanced the ubiquitination and proteasome-dependent loss of ChAT protein. Importantly, the effects of HSP inhibition were greater for mutant ChAT proteins (P17A/P19A-ChAT and CMS-related V18M- and A513T-ChAT) compared to wild-type ChAT. HSPs can promote ubiquitination and degradation of terminally misfolded proteins through cooperative interaction with the E3 ubiquitin ligase CHIP/Stub1, and while we show that ChAT interacts with CHIP in situ, siRNA-mediated knock-down of CHIP had no effect on either wild-type or mutant ChAT protein levels. However, inhibition of the endoplasmic reticulum (ER)- and HSP-associated co-chaperone p97/VCP prevented degradation of ubiquitinated ChAT. Together, these results identify novel mechanisms for the functional regulation of wild-type and CMS-related mutant ChAT by pro-stabilizing HSPs and the pro-degradative co-chaperone p97/VCP that may have broader implications for ChAT function during cellular stress and disease.